ChemInform Abstract: Ligand‐Enabled Cross‐Coupling of C(sp3)—H Bonds with Arylboron Reagents via Pd(II)/Pd(0) Catalysis. Issue 29 (22nd July 2014) - Chan, Kelvin S. L.; Wasa, Masayuki; Chu, Ling; Laforteza, Brian N.; Miura, Masanori; Yu, Jin‐Quan
Abstract A mono‐N‐protected amino acid ligand enables the Pd‐catalyzed coupling of γ‐C(sp3)‐H bonds in triflyl‐protected amines with arylboron reagents.